Effect of Mn doping on the chemical synthesis of interconnected nanoflakes-like CoS thin films for high performance supercapacitor applications. Issue 18 (15th December 2018) - Shinde, S.K.; Jalak, M.B.; Kim, S.Y.; Yadav, H.M.; Ghodake, G.S.; Kadam, A.A.; Kim, D.-Y.
Abstract: Herein, supercapacitor developed using Mn-doped CoS thin films (1–5% Mn) were prepared using the successive ionic layer adsorption and reaction (SILAR) method. The effect of the Mn-doped CoS thin films on the structural, morphological, and supercapacitor properties were studied using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), and electrochemical evaluation. Doping up to 3% Mn lead to improvements in peak intensity. Also, the morphological results indicated that doping of Mn affected the CoS nanostructures. The 3% Mn-doped CoS electrodes had an interconnected nanoflakes-like nanostructure, with a high porosity compared to the other electrodes. XPS data strongly supported the XRD results. The Mn-doped CoS electrodes showed a higher capacitance (621 F g −1 ) than the other electrodes, and electrochemical impedance spectroscopy indicated that the 3% Mn-doped CoS electrode was highly conductive. The characteristics of the 3% Mn-doped CoS electrode proved its applicability in supercapacitors. Graphical abstract: Specific capacitance of Mn doped CoS electrodes deposited at various Mn percentage using SILAR method. Highlights: Novel route for the synthesis of Mn doped CoS thin films. Different nanostructure of Mn doped CoS thin films. 3%Mn doped CoS electrodes show the higher reactive area. 3%Mn doped CoS electrodes demonstrated outstanding supercapacitive performance.